2018
DOI: 10.3389/fmicb.2018.01479
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Epigenetic Inheritance Under Environmental Stress by Genome-Wide DNA Methylation Profiling in Cyanobacterium

Abstract: Epigenetic modifications such as DNA methylation are well known as connected with many important biological processes. Rapid accumulating evidence shows environmental stress can generate particular defense epigenetic changes across generations in eukaryotes. This transgenerational epigenetic inheritance in animals and plants has gained interest over the last years. Cyanobacteria play very crucial role in the earth, and as the primary producer they can adapt to nearly all diverse environments. However, few know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…raciborskii), we observed that this species was one of the most sensitive freshwater species to increased salinity; however, after multigenerational exposure to low levels of salinity, the effective conductivities more than doubled. Cyanobacteria can adapt to nearly all environments and, as reported above for daphnids, epigenetic traits might also be underlying that success [77]. For instance, 72 h of nutrient depletion in the model cyanobacterium Synechocystis were enough to induce DNA methylation in a partially inheritable fashion [77].…”
Section: (C) Multigenerational Exposure To Low Levels Of Salinitymentioning
confidence: 92%
See 1 more Smart Citation
“…raciborskii), we observed that this species was one of the most sensitive freshwater species to increased salinity; however, after multigenerational exposure to low levels of salinity, the effective conductivities more than doubled. Cyanobacteria can adapt to nearly all environments and, as reported above for daphnids, epigenetic traits might also be underlying that success [77]. For instance, 72 h of nutrient depletion in the model cyanobacterium Synechocystis were enough to induce DNA methylation in a partially inheritable fashion [77].…”
Section: (C) Multigenerational Exposure To Low Levels Of Salinitymentioning
confidence: 92%
“…Cyanobacteria can adapt to nearly all environments and, as reported above for daphnids, epigenetic traits might also be underlying that success [77]. For instance, 72 h of nutrient depletion in the model cyanobacterium Synechocystis were enough to induce DNA methylation in a partially inheritable fashion [77]. Though salinity proved to be a limiting factor on the population growth of Cy.…”
Section: (C) Multigenerational Exposure To Low Levels Of Salinitymentioning
confidence: 93%
“…As noted above, transgenerational effects inherited without induction of any change in DNA sequence have received considerable attention during the past two decades (Burggren, 2016;Hu et al, 2018;Inbar-Feigenberg et al, 2013;Jablonka and Raz, 2009). The study of transgenerational epigenetic effects had been linked mostly with maladaptive implications in human-focused disciplines such as medicine (Baccarelli et al, 2010).…”
Section: Potential Mechanisms For Epigenetic Inheritance Of Larval Phmentioning
confidence: 99%
“…PCC 7120 (Matveyev et al, 2001; Elhai, 2015). There are some hints that the cyanobacterial methylome could be modified in response to certain environmental cues (Walworth et al, 2017; Hu et al, 2018), but the overall role of DNA methylation beyond RM systems has not been studied in cyanobacteria so far.…”
Section: Introductionmentioning
confidence: 99%